IMPLEMENTASI PEMBLOKAN SITUS DENGAN FIREWALL LAYER 7 PROTOCOL MENGGUNAKAN METODE NDLC PADA ROUTER MIKROTIK - Sonny Aditya Imawan; Saruni Dwiasnati (MULTINETICS, 2025)
In the current era of technological advancement, companies' dependency on computer networks is increasing. Intensive internet usage during working hours presents challenges in efficiently managing bandwidth. Uncontrolled activities such as accessing social media, playing online games, and streaming videos can degrade network quality, disrupt productivity, and cause service dissatisfaction. This research aims to enhance the efficiency of network usage in the company by focusing on reducing bandwidth due to uncontrolled internet usage, particularly by identifying and blocking access to websites unrelated to work activities using Firewall Layer 7 Protocol. Approximately 45% of employees frequently visit other sites during working hours. System development is carried out using the Network Development Life Cycle (NDLC) method, which illustrates the continuous cycle of computer network development. Testing results in the research using the BlackBox method with Winbox software to assess the planned system performance successfully blocked sites, online games, and increased bandwidth; after implementation, the bandwidth achieved was above 50Mbps during working hours. This method is expected to provide effective solutions to improve network quality, optimize bandwidth usage, and support overall company productivity.